RETRACTED: Analisis Hukum Terkait Kerja Lembur Melebihi Batas Waktu Terhadap Hak Asasi Manusia - Nurun Isnaini (Fakultas Hukum Dehasen, 2023)
RETRACTION NOTICE Following up on the review of articles published in Jurnal Hukum Sehasen carefully, thoroughly, and considering the article entitled